Reimagining carbon emission mitigation in sustainable agriculture: uncovering farmers’ propensity for straw recycling - Hou, Jiaqi; Yu, Chengze; Xu, Yan; Li, He; Cai, Andong; Ye, Meiying; Ma, Zhifei; Cui, Guannan; Zhu, Jie (Frontiers in Sustainable Food Systems, 2023)
The issue of carbon emission reduction for sustainable agriculture in rural areas has gained significant attention in China. Farmers play a crucial role as key implementers and active participants in this process, highlighting the significance of their awareness of carbon emission reduction. Straw, as the primary source of carbon emissions in rural areas, is a key component of rural carbon emission reduction efforts. This study focuses on 26 representative villages in Heilongjiang Province to analyze the current status of straw production and resource utilization in the context of rural carbon emission reduction. By employing the planned behavior theory in combination with structural equation modeling, the study aims to explore the analysis and prediction of farmers’ willingness to reduce carbon emissions. The findings reveal that maize and rice crops are the primary sources of straw in Heilongjiang Province, with the existing policies primarily focusing on the practice of returning straw to the field. However, the burning of straw in the field remains prevalent due to factors such as immature conversion technologies, high costs, low benefits, and limited recycling rates of enterprises, subsequently leading to increased carbon emissions. Moreover, farmers’ habits of stacking or burning straw in the field significantly influence straw utilization and carbon emission reduction awareness. To address these issues, the government should formulate appropriate straw recycling policies based on the specific circumstances and needs of farmers. Additionally, implementing comprehensive straw utilization policies becomes more effective when farmers have positive perceptions and awareness of carbon emission reduction and straw recycling. In conclusion, the government should develop diverse modes of straw resource utilization and field management tailored to local conditions. Furthermore, strengthening research and development efforts, providing technical training, and offering policy support are essential for promoting carbon emission reduction in rural areas.